Design of an unmanned ground vehicle - Yang, Eric Neng Zhou (2016)
The rate of human crimes in today’s world are increasing and it prompts the safety measures to be taken without the risk of human lives. With the current advanced technology, robots can help us achieve this goal. This robot is an Unmanned Ground Vehicle that can monitor enemy attacks and intruders to collect initial information in a more efficient and flexible manner, without risking humans to the exposure of hazard in an unknown environment. In this project, a Raspberry Pi controlled 4-wheel vehicle will be assembled with the ability of navigating through a series of GPS coordinates with a camera mounted on top of the vehicle to get a live broadcast of the surroundings.